Clinicopathological correlations between colorectal cancer and genetic mutations - Alexandra-Alina Vesa; Octavian Maghiar; Ovidiu Pop; Monica Boros; Andrei Pascalau; Adrian Maghiar (Romanian Journal of Medical Practice, 2023)
Objective. Colorectal cancer is an oncological pathology that, unfortunately, has increased in terms of incidence in recent years. The presence of KRAS and BRAF mutations in colorectal cancer has significant clinical implications. As a result we want to conduct research that analyzes the impact of these mutations on patients diagnosed with colorectal cancer and also to observe the clinicopathological differences between mutant and wild-type tumors. Material and methods. We conducted a retrospective study in the period 2018-2022, including 118 patients diagnosed with colorectal cancer. The patients were subsequently divided into two groups equal in number of patients, depending on the presence or absence of mutations. Outcomes. After analyzing the data we were able to identify several differences between the two groups, regarding the histopathological type - mucinous correlated with the mutant tumors, the degree of infiltration of the locoregional lymph nodes (more N+ cases in the mutant group), the location of the primary tumor (right colon within the mutant tumors, the rectosigmoid region in the wild-type group), the location of secondary tumors (pulmonary ones with a triple incidence in the mutant group). Conclusions. The study of genetic mutations and their role in colorectal cancer has provided valuable insights into the underlying mechanisms of this complex disease. It is an ever-evolving field that promises to have a profound impact on patient care, ultimately leading us toward more effective prevention, early detection, and personalized therapies for colorectal cancer patients. By leveraging genetic information, clinicians can optimize treatment plans, minimize side effects, and increase the chances of successful outcomes for individual patients.